Study of Cross Match to Transfusion Ratio in Patients Undergoing Elective Orthopedic Surgery - Haider Ali, Syed Muhammad; Farhan, Aatir; Razzaq, Asim; Sami Ur Rehman; Ali, Khawar (Indus Journal of Bioscience Research, 2025)
Background: Blood transfusions are a common part of elective orthopedic surgeries, yet there is often significant wastage in the utilization of cross-matched blood. Optimizing blood usage through efficient blood ordering practices is essential for reducing costs and resource waste. However, the effectiveness of such practices needs further investigation in different hospital settings. Objective: To determine the frequency of blood transfusion, transfusion probability, and cross match to transfusion ratio in patients undergoing elective orthopedic surgery. Study Design: Descriptive cross-sectional study. Duration and Place of Study: This study was conducted from April 2024 to October 2024 at the Department of Anesthesia, Doctors Hospital and Medical Centre, Lahore. Methodology: A total of 92 patients aged 25–70 years, undergoing elective orthopedic surgeries, were enrolled. Patient demographics and clinical data, including comorbidities, surgical type, and blood ordering details, were recorded. The C/T ratio and TP were calculated to assess blood usage efficiency. Results: The mean age of the patients was 45.2 ± 14.1 years, and 64.1% had blood reserved for transfusion. The mean C/T ratio was 2.13 ± 2.38. The transfusion rate was 21.7%, with a higher transfusion probability observed in patients with diabetes (46.2%) and those undergoing lower limb surgeries (66.7%). Conclusion: The study highlights significant blood wastage in elective orthopedic practices and a disproportionate transfusion rate. Implementing a Maximum Surgical Blood Ordering Schedule can optimize resource utilization. Our findings align with previous studies, reinforcing the need for strict adherence to evidence-based practices to minimize waste and enhance the efficient use of blood in orthopedic surgeries.